THE ROLE OF ENGINEERING PEDAGOGY IN THE SOLUTION OF SECURITY PROBLEMS ON AUTOMOBILE TRANSPORT AND IN THE SPHERE OF ROAD MAINTENANCE - Yury V. Trofimenko; Zoya S. Sazonova; Tatyana V. Fedyukina (Высшее образование в России)
An important factor in providing security in technosphere is the level of professional competency of the engineers - Bachelor’s, Master’s and Specialist’s degree holders, - who design, create and operate objects of the infrastructure. In the paper we analyze the role of engineering pedagogy in the processes of preparation of competent engineers at technical university MADI to solve the tasks of providing security in technosphere and of subsequent improvement of their qualifications.